Effects of different nitrogen fertilizers on two wheat cultivars: An integrated approach. (22nd October 2018) - Vita, Federico; Giuntoli, Beatrice; Arena, Simona; Quaranta, Fabrizio; Bertolini, Edoardo; Lucarotti, Valentina; Guglielminetti, Lorenzo; Alessio, Massimo; Scaloni, Andrea; Alpi, Amedeo
Abstract: Investigation of cultivated plant physiology grown under low energy input plays an important role to indicate their fitness to the new environmental conditions. The durum‐wheat cultivars Creso and Dylan were tested to evaluate the growth, production, and proteomic and transcriptomic profiles of the crop under different synthetic and organic nitrogen fertilization regimes. In this work, a two‐dimensional gel electrophoresis (2‐DE) approach combined with liquid chromatography–mass spectrometry (LC–MS) was used to investigate the protein changes induced by the use of different nitrogen sources (hydrolysate of proteins 1 and 2, rhizovit, synthesis, leather) on wheat plants. Proteomic studies were integrated with qPCR analysis of genes related to glutamine synthetase/glutamine‐2‐oxoglutarate aminotransferase (GS‐GOGAT) and tricarboxylic acid (TCA) metabolic pathways because most relevant for nitrogen‐dependent plants growth. The proteomic analysis lead to the isolation of 23 spots that were able to distinguish the analyzed samples. These spots yielded the identification of 60 proteins involved in photosynthesis, glycolysis, and nitrogen metabolism. As an example, the quinone oxidoreductase‐like protein and probable glutathione S ‐transferase GSTU proteins were identified in two spots that represents the most statistically significant ones in Dylan samples. Transcript analysis indicated that related genes exhibited different expression trends; the heat map also revealed the different behaviors of the hydrolysates of the proteins 1 and 2 nitrogen sources. The effects of nitrogenous fertilizers at the proteomic and agronomic levels revealed that plants fertilized with synthesis or rhizovit gave the best results concerning yield, whereas rhizovit and protein hydrolysates were most effective for proteins content in the grain (% of dry weight). Therefore, all parameters measured in this study indicated that different kinds of nitrogen fertilization used have a relevant impact on plant growth and production.